Ontmoetingen 2007. - De Brabander, Trees; Moijson, Machteld (Lochristi : Lo-Art Lochristi, 2007)
Boone, Kathleen ; De Brabander, Trees ; Bracke, Rita ; Braet, Kristien ; Bundervoet, Marcus ; Verhaeghe, Tine ; Van Cleemput, Miriam ; De Clercq, Daniel Gustaaf ; Van Durme, Sofie ; Haegens, Jan ; Lootens, Marjolijn ; Merckx, Hilde ; Moijson, Machteld ; Praet, Roger ; Reynebau, Kris ; Schatteman, Katrijn ; Taghon, Freddy ; Vanrijckeghem, Patrick ; Verschraegen, Marjan ; De Vos, Marleen ; De Wouwe, Charlotte
Nederlands
Exhibition. Ontmoetingen 2007. Lo-Art Lochristi. 2007-11-15
boek